A systematic review of interventions by healthcare professionals to improve management of non-communicable diseases and communicable diseases requiring long-term care in adults who are homeless. Issue 4 (7th April 2018) - Hanlon, Peter; Yeoman, Lynsey; Gibson, Lauren; Esiovwa, Regina; Williamson, Andrea E; Mair, Frances S; Lowrie, Richard
Abstract : Objective: Identify, describe and appraise trials of interventions delivered by healthcare professionals to manage non-communicable diseases (NCDs) and communicable diseases that require long-term care or treatment (LT-CDs), excluding mental health and substance use disorders, in homeless adults. Design: Systematic review of randomised controlled trials (RCTs), non-RCTs and controlled before–after studies. Interventions characterised using Effective Practice and Organisation of Care (EPOC) taxonomy. Quality assessed using EPOC risk of bias criteria. Data sources: Database searches (MEDLINE, Embase, PsycINFO, Scopus, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Applied Social Sciences Index and Abstracts (ASSIA) and Cochrane Central Register of Controlled Trials), hand searching reference lists, citation searches, grey literature and contact with study authors. Setting: Community. Participants: Adults (≥18 years) fulfilling European Typology of Homelessness criteria. Intervention: Delivered by healthcare professionals managing NCD and LT-CDs. Outcomes: Primary outcome: unscheduled healthcare utilisation. Secondary outcomes: mortality, biological markers of disease control, adherence to treatment, engagement in care, patient satisfaction, knowledge, self-efficacy, quality of life and cost-effectiveness. Results: 11 studies were included (8 RCTs, 2 quasi-experimental and 1 feasibility) involving 9–520 participants (67%–94% male, median age 37–49 years). Ten from USA and one from UK. Studies included various NCDs (n=3); or focused on latent tuberculosis (n=4); HIV (n=2); hepatitis C (n=1) or type 2 diabetes (n=1). All interventions were complex with multiple components. Four described theories underpinning intervention. Three assessed unscheduled healthcare utilisation: none showed consistent reduction in hospitalisation or emergency department attendance. Six assessed adherence to specific treatments, of which four showed improved adherence to latent tuberculosis therapy. Three concerned education case management, all of which improved disease-specific knowledge. No improvements in biological markers of disease (two studies) and none assessed mortality. Conclusions: Evidence for management of NCD and LT-CDs in homeless adults is sparse. Educational case-management interventions may improve knowledge and medication adherence. Large trials of theory-based interventions are needed, assessing healthcare utilisation and outcomes as well as assessment of biological outcomes and cost-effectiveness.